Strategies for Success in Human Development - Gustav Ranis; Frances Stewart (Yale University, Economic Growth Center, 2000)
This paper analyzes the various policy dimensions which have contributed to successful human development (HD) performance in developing countries over the past three decades. We identify the four best HD performers in each of the regions, taking their level of life expectancy and infant mortality, as well as improvements in these dimensions over time, as the indicators. Examining the elements underlying HD performance reveals that a variety of combinations of vigorous economic growth, government social expenditure ratios and equitable distribution of income can lead to successful human development. None of the 'successful' countries performed well in every dimension conducive to HD success; rather, it appears that doing well with respect to some elements can compensate for relative weakness in others, even weak economic growth. It does appear, however, that one condition crucial in every case was a relatively high female primary enrolment ratio; in many cases the extent of female control over the family's income also proved significant.
Keywords: 330; Lebensqualität; Öffentliche Sozialausgaben; Entwicklungsländer